Binding Energies of Hydrogen-Bonded cis-Amide and Nucleobase Dimers: An Evaluation of DFT Performance - Jann A. Frey; Samuel Leutwyler (CHIMIA, 2005)
The understanding of biological processes at the molecular level demands accurate knowledge of the nonbonded interactions that control the geometries, binding energies and dynamics of the supramolecular structures involved. High level ab initio methods are still prohibitively expensive for large systems, but certain density functional (DFT) methods can provide cost-effective alternatives. The performance of six different functionals (BLYP, B3LYP, X3LYP, PBE, PW91, and mPW91) for the calculation of the doubly hydrogen-bonded cis-amide dimers (formamide)2 and (2-pyridone)2 have been tested. Their N-H···O hydrogen bond motifs occur between many nucleobases, peptides, and proteins. Binding energy benchmarks using ab initio MP2 calculations and basis set extrapolations to the complete basis set (CBS) limit with the Dunning aug-cc-pVXZ (X=D,T,Q) basis set series have been established. These yield D?e = ?14.80 kcal/mol for (formamide)2 and ?22.63 kcal/mol for (2PY)2. Of the six functionals, PW91 consistently gives the best agreement with the MP2 basis-set limit binding energies, closely followed by PBE. The mPW91, B3LYP and the recently proposed X3LYP functionals are in less good agreement. The BLYP functional underestimates the interaction strengths by 20–25% and is not recommended. As an application the hydrogen-bond isomerization equilibria for the Sugar-edge, Watson-Crick and Wobble isomers of the dimers 2-pyridone·uracil and 2-pyridone·thymine from first principles are computed and compared to experiment.